Association of the angiotensin II type I receptor gene +1166 A>C polymorphism with hypertension risk : evidence from a meta-analysis of 16474 subjects - Niu, Wenquan; Qi, Yue (Hypertension research, 2010)
Mounting evidence suggests the potential susceptibility of individuals with a mutation in the angiotensin II type I receptor ( AT1R ) gene to hypertension. One polymorphism, +1166 A>C, has been extensively studied, but the results have often been irreproducible. We therefore aimed to meta-analyze all available case–control studies from the English language literature to explore the association of this polymorphism with hypertension. A total of 22 studies with 24 populations involving 8249 patients and 8225 controls were identified as of 25 February 2010. A random-effects model was performed regardless of the between-study heterogeneity. The study quality was assessed in duplicate. The data were analyzed using RevMan software (version 5.0.23). Overall, the presence of the +1166 C allele significantly conferred an increased risk of hypertension (odds ratio (OR)=1.14; 95% confidence interval, 1.00–1.30; P =0.05). Under the assumption of three genetic modes of inheritance, an elevated hypertension risk was observed for each comparison (codominant: AC vs . AA, OR=1.10 ( P =0.20) and CC vs . AA, OR=1.21 ( P =0.36); dominant: OR=1.13 ( P =0.09); recessive: OR=1.21 ( P =0.36)). Upon stratification by study design, more obvious associations were observed for the population-based design, whereas there were no changes in direction and only slight changes in magnitude upon stratification by sample size and geographical area. No publication biases were indicated by the fail-safe number. Our study pooled previous findings and showed that the AT1R +1166 C allele conferred an increased risk of hypertension. We suggest that confirmation in a large, well-designed study or from functional aspects of this polymorphism is critical.